Erythema and Induration of Bacillus Calmette-Guérin Scar Associated With Multisystem Inflammatory Syndrome in Children in Japan: A Case Report - Tsuboya, Naoki; Makino, Hirotoshi; Mitani, Yoshihide; Ito, Michiko; Ohya, Kazunobu; Morimoto, Mari; Hanaki, Ryo; Yodoya, Noriko; Ohashi, Hiroyuki; Sawada, Hirofumi; Sugiyama, Kenji; Hirayama, Masahiro (Frontiers in Pediatrics, 2022)
Multisystem Inflammatory Syndrome in Children (MIS-C) is a rare febrile disorder with multisystem organ involvement temporally associated with coronavirus 2019 infection (COVID-19) and frequently exhibits features mimicking Kawasaki disease (KD), another febrile disorder in children. The pathogenesis and the full clinical spectrum of MIS-C is poorly understood: It is still unclear whether MIS-C and KD are different syndromes or represent a common spectrum. The erythema and induration of Bacillus Calmette-Guérin (BCG) scar is one of the characteristic findings of KD, and is useful for the diagnosis in countries where BCG vaccination is mandated in infancy. Furthermore, such findings in BCG scar were also reported after SARS-CoV-2 vaccination, which may be related to molecular mimicry. However, there are no reports of changes at the BCG scar in MIS-C cases. Here, we report a case of MIS-C in a 3-year-old Hispanic boy in Japan, with erythema and induration at the BCG scar. The patient received BCG vaccination at 16 months of age in Japan. Four weeks before the onset, he had positive PCR results for SARS-CoV-2 following household outbreak, although he was asymptomatic. He presented with fever and gastrointestinal symptoms, followed by the appearance of all six principal findings of complete KD. He exhibited congestive heart failure, following intravenous immunoglobulin (IVIG) therapy. He was diagnosed with MIS-C based on characteristic mucocutaneous and gastrointestinal symptoms, decreased cardiac function, and coagulopathy, in addition to laboratory data consistent with MIS-C. The BCG finding was present from the early stage of the disease. The patient was refractory to two doses of IVIGs, and the third IVIG plus prednisolone resulted in defervescence and improvement in heart failure. No coronary involvement was observed. This is the first case of erythema and induration at the BCG scar associated with MIS-C accompanied by KD features, which may give clinical and mechanistic insights in the understanding of the disease. Since the full spectrum of MIS-C is still evolving and both of them are syndromes with overlapped clinical features, further studies are warranted for deep phenotyping of MIS-C with KD features relative to KD in countries with mandatory BCG programs in infancy.